Analisis penggunaan alat magnetisasi bahan bakar secara elektromagnetik terhadap unjuk kerja mesin empat langkah satu silinder - I.M. Mara; I.W. Joniarta; I.B. Alit; I.M.A. Sayoga; I.M. Nuarsa (Universitas Mataram, 2018)
The effort to increase fuel economy and to thrift the usage of fossil fuel is becoming main focus in the entire the world. One of those efforts is by using electromagnetic field in order to increase the quality of the combustion process and reducing fuel consumption.This research investigates the effect of the number of cooper wire winding on electromagnetic field on engine torque, engine power and fuel consumption of 100 cc four stroke single cylinder gasoline engine. The numbers of cooper wire windings are, 3000, 4000 and 4500. The engine performance was analyzed at several engine rotations. The result shows that there is an increase of engine power by 13% and on the other hand the fuel consumption reduced by 11% on 4000 windings at 6000 rpm.